PEMBATALAN PERJANJIAN YANG DILAKUKAN OLEH SALAH SATU PIHAK - Cahyono, Rudi; Abdur Rohim; Vera Wati (JUSTNESS - Jurnal Hukun dan Agama, 2025)
Abstract This article discusses the phenomenon of cancellation of an agreement carried out by one of the parties in contract law. Cancellation of an agreement can occur for various reasons, such as violation of agreed terms, inability to fulfill obligations, or elements of fraud and coercion. In this study, the author analyzes the legal basis governing the cancellation of agreements, including provisions in the Civil Code (KUHPer) and general principles of contract law. Apart from that, this article also explores the legal consequences of canceling an agreement, both for the party canceling it and the party who is injured, as well as steps that can be taken to resolve disputes that arise as a result of the cancellation. This article aims to provide a deeper understanding of the legal implications of canceling an agreement and the importance of complying with the terms agreed upon in the contract. In this way, readers can understand the legal dynamics related to canceling agreements and the preventive steps that can be taken to avoid future conflicts. Keywords : contract law, cancellation